TYPE OF MESONEPHRIC GYNECOLOGICAL CANCER - Coz Carranza, Javier (2015)
Mesonefric three cases of cancer are studied, one in the uterus and two in the ovary treated at the Gynecology Department of the Hospital E. Rebagliati during the years 1983 to 1987. The patients with uterine neoplasia corresponded to stage III, he died in very short time, where the disease was localized in the ovary were classified as stage Ic and survived two years without evidence of disease. Used treatment modalities are exposed and discussed the issue.